Optimasi Kesiapan Kerja Siswa SMK Master Indonesia Bogor Melalui Pelatihan Berbasis Industri - Kusuma , Harun Indra; Alfikri, M Reza; Wardani, Ega (Pencerah, 2023)
Community service at Master Indonesia Vocational High School (SMK) Bogor in 2022 aims to improve the competence of vocational teachers and the quality of vocational education. The program consists of two phases, namely Phase I in February and Phase II in May. In the planning phase, an initial evaluation of teachers' needs was used to design a responsive training program. The implementation phase provided training and technical support to teachers, resulting in significant improvements in teaching skills and technical knowledge. The assessment phase, measures the effectiveness of the program and forms the basis for program improvements in Phase II. The program is updated based on teacher and student responses. The continuous evaluation phase, enabling the monitoring of long-term impacts, including improvements in teachers' competencies and students' motivation. In conclusion, the program successfully improved the quality of vocational education and motivated students to pursue careers in vocational fields. These results suggest that investments in vocational education can create significant positive changes in students' preparation for the competitive world of work.